Use of food/dietary supplements in the geriatric population and its possible effects on their drug regimen in a tertiary government hospital in Metro Manila - Bautista, Angeli Coleen S.; Cagaoan, Theresa Marie M.; Caseres, Glecie A. (2017)
One of the problems in the elderly is malnutrition due to the physiological changes brought by ageing and underlying diseases. This could then lead to the consumption of food/dietary supplements, aside from the medicines prescribed by their physician. However, with this, there is a risk of having potential drug-supplement interaction and thus, it is important to understand the trends and perceived knowledge of the geriatric population on the use of these supplements. This study aims to evaluate the use of food/dietary supplements and assess its possible effects to the drug regimen. It is a descriptive, cross sectional study design and consists of a survey-interview to patients, aged 60 and above, in the general clinics of the Out-Patient Department in Philippine General Hospital. The results showed that 118 (74.80%) out of 159 participants were currently taking food/dietary supplements. Vitamin B Complex, Multivitamins, and Mangosteen were the frequent supplements taken by the elderly. In addition, they have different perceived knowledge when it comes to food/dietary supplements, hence affecting their use. Only a few cases of actual potential drug-food/supplement interaction were detected in the patient's drug regimen involving blood-thinning agents. Among the most commonly used drugs and food/dietary supplement, there were identified possible interactions that warrant supervision from healthcare providers to ensure optimal use of medications.